Aerodynamic investigation of tucked positions in alpine skiing - Elfmark, O.; Teigen Giljarhus, K. E.; Fang Liland, F.; Oggiano, L.; Reid, R. (Journal of Biomechanics, 2021)
The purpose of this investigation was to examine the aerodynamics of tucked positions in competitive alpine skiing. To further our understanding of how a skier`s position affects the air flow and the resulting aerodynamic drag, a combination of both experimental and simulation methods was used. This study focused in particular on the effect of skier torso and thigh angles relative to the air flow direction, as these two angles have been previously found to be important determinants of aerodynamic performance in tucked positions. Two top 30 world-ranked skiers were investigated in two different wind tunnels, and the results were compared with Computational Fluid Dynamics (CFD) simulations performed using a 3D scan of one of the athlete. To quantify the effect of torso and thigh angles on skier drag, changes in drag were measured relative to baseline positions.